PEMBERDAYAAN PEREMPUAN MELALUI SEKOLAH MEMBATIK DEWI ANOM DI DESA WISATA WRINGINANOM - Putri, Rizky Yuliana Prasetyo; Amalia, Siti Afidhotun; Ulum, Bahrul; Pitaloka, Merlin Dhiya; Aulia, Baiq Assyifa Ilyatul; Setyorini, Heni Sri Enda; Septia, Vina Aulia; Nurriskiani, Sitti; Atsar, Anisa Wahyu Adzkiya; Hanifah, Aisyah Nur; Revanda, Fahmi Axel; Nabilla, Shany Putri; Humaidah, Nurul (Universitas Padjadjaran, 2026)
Wringinanom Village, recognized as the gateway to Bromo tourism and a recipient of the 2024 Indonesian Tourism Village Award (ADWI), faces limited participation of women in village development. This community service program established the “Dewi Anom Batik School” as a platform for women’s empowerment and independence through batik-making training, entrepreneurship education, financial management, and product marketing. The program was implemented through needs assessment, curriculum design, technical training, mentoring, stakeholder networking, as well as monitoring and evaluation. As a result, a non-formal batik school integrated with the village tourism program was established, local batik products featuring the “Sedaer Dewi Anom” motif were created, women’s business groups were formed, and participants’ knowledge and skills increased by 80%. Overall, this program strengthens women’s roles in tourism village development while fostering a culture-based creative economy in Wringinanom.Desa Wringinanom, yang dikenal sebagai pintu gerbang pariwisata Bromo dan penerima Anugerah Desa Wisata Indonesia (ADWI) 2024, masih menghadapi keterbatasan partisipasi perempuan dalam pembangunan desa. Program pengabdian masyarakat ini membentuk “Sekolah Membatik Dewi Anom” sebagai wadah pemberdayaan dan peningkatan kemandirian perempuan melalui pelatihan membatik, kewirausahaan, pengelolaan keuangan, dan pemasaran produk. Metode pelaksanaan meliputi asesmen kebutuhan, perancangan kurikulum, pelatihan teknis, pendampingan, jejaring pemangku kepentingan, serta pemantauan dan evaluasi. Hasil program menunjukkan terbentuknya sekolah membatik nonformal yang terintegrasi dengan desa wisata, terciptanya produk batik lokal bermotif Sedaer Dewi Anom, terbentuknya kelompok usaha perempuan, serta peningkatan pengetahuan dan keterampilan peserta sebesar 80%. Dengan demikian, program ini memperkuat peran perempuan dalam pembangunan desa wisata sekaligus mendorong pengembangan ekonomi kreatif berbasis budaya lokal di Desa Wringinanom.